Dihydrobenzisoxazole-4-one compounds are novel selective inhibitors of aldosterone synthase (CYP11B2) with in vivo activity. Issue 5 (1st March 2018) - Meyers, Kenneth; Cogan, Derek A.; Burke, Jennifer; Arenas, Raquel; Balestra, Michael; Brown, Nicholas F.; Chen, Zhidong; Cerny, Matthew A.; Clifford, Holly E.; Colombo, Federico; Fader, Lee; Frederick, Kosea S.; et al.
Graphical abstract: Abstract: 6, 7-Dihydro-5H-2, 1-benzisoxazol-4-one analogs are potent inhibitors of aldosterone synthase (CYP11B2) with selectivity over the highly homologous enzyme cortisol synthase (CYP11B1). These compounds are unique among inhibitors of CYP11B2 in their lack of a strong-heme binding group such as a pyridine or imidazole. Poor metabolic stability in hepatocyte incubations was found to proceed via a reduction of the isoxazole ring. While the enzyme responsible for the reductive metabolism remains unknown, the rate of metabolism could be attenuated by the addition of polar functionality. The in vitro CYP11B2 potency and selectivity were confirmed in vivo in a cynomolgus monkey model by the inhibition of ACTH stimulated aldosterone production without impacting plasma cortisol concentrations.